1586 Minor Hypospadias: The "Tip of the Iceberg" of the Partial Androgen Insensitivity Syndrome. (October 2012) - Kalfa, N; Philibert, P; Audran, F; Bashamboo, A; Lehors, H; Haddad, M; Guys, JM; Reynaud, R; Alessandrini, P; Wagner, K; Kurzenne, JY; Bastiani, F; et al.
Abstract : Background and Aims: Alterations in the androgen sensitivity pathway have been identified in severely undermasculinized boys, and mutations of the androgen-receptor gene (AR) are usually found in partial or complete androgen insensitivity syndrome. The aim of this study was to determine whether even the most minor forms of isolated hypospadias are associated with AR mutations and thus whether all types of hypospadias warrant molecular analysis of the AR. Methods: 292 Caucasian children presenting with isolated hypospadias (no micropenis, no cryptorchidism) and 345 controls were included prospectively. Mutational analysis of the AR through direct sequencing (exons 1–8) was performed. Results: Five missense mutations of the AR were identified in 9 patients with glandular or penile anterior (n=5), penile midshaft (n=2) and penile posterior (n=2) hypospadias, i.e., 3%: p.Q58L (c.1288 A>T), 4 cases of p.P392S (c.2289 C>T), 2 cases of p.A475V (c.2539 C>T), p.D551H (c.1651 G>C) and p.Q799E (c.3510 C>G). None of these mutations was present in the control group. Four mutations are novel findings since 1 has never been reported to date (p.D551H) and 3 have never been reported in patients with genital malformation but only in isolated infertility: p.Q58L, p.P392S, and p.A475V. It is notable that micropenis, a cardinal sign of AIS, was not present in any patients. Conclusion: AR mutations may play a role in the cause of isolated hypospadias, even in the most minor forms. Identification of this underlying genetic alteration is important for proper diagnosis and may significantly improve the follow-up of these patients during puberty, especially regarding future fertility.